Chest computed tomography‐derived muscle mass and quality indicators, in‐hospital outcomes, and costs in older inpatients. Issue 2 (17th February 2022) - Shen, Yanjiao; Luo, Li; Fu, Hongbo; Xie, Lingling; Zhang, Wenyi; Lu, Jing; Yang, Ming
Abstract: Background: Muscle mass and muscle quality assessed by computed tomography (CT) have been associated with poor prognosis in oncology and surgery patients, but the relevant evidence was limited in older patients. We hypothesized that muscle mass and muscle quality indicators derived from opportunistic chest CT images at the 12th thorax vertebra level (T12) could predict in‐hospital death, length of hospital stay (hospital LOS), and hospital costs among older patients in acute care wards. Methods: We conducted a prospective cohort study. Older patients admitted to the acute geriatric wards of a teaching hospital were continuously recruited. Chest CT images were analysed using SliceOmatic software. The skeletal muscle area, skeletal muscle radiodensity, and intermuscular adipose tissue (IMAT) at the T12 level were measured. Skeletal muscle index (SMI) was calculated using skeletal muscle area divided by body height squared. Results: We included 1135 older patients with a median age of 80 years (interquartile range, 73 to 85 years), 498 (44%) were women, 148 (13%) patients died during hospitalization. The SMI and SMD were negatively correlated to age (ρ = −0.11, P < 0.001, ρ = −0.30, P < 0.001, respectively), whereas the IMAT was positively correlated to age (ρ = 0.27, P < 0.001). Compared with survivors, dead patients had significantly lower SMI in men ( P < 0.001) but not in women ( P = 0.760). After adjusting for sex and other potential confounders, the SMI [increased per 1 cm 2 /m 2, odds ratio (OR) 0.96, 95% confidence interval (CI) 0.93 to 0.99] and SMD (increased per 1 Hounsfield unit, OR 0.93, 95% CI 0.90 to 0.96) were negatively and independently associated with in‐hospital death, whereas the IMAT (increased per 1 cm 2, OR 1.09, 95% CI 1.05 to 1.14) was independently and positively associated with in‐hospital death. None of the SMI, SMD, or IMAT was significantly related to long hospital LOS or increased hospital costs. Conclusions: Chest CT‐derived muscle mass indicator (T12 SMI) and muscle quality indicators (T12 SMD and T12 IMAT) may serve as prognostic factors for predicting in‐hospital death among older inpatients. Opportunistic chest CT images might be an overlooked resource for measuring muscle mass and muscle quality and for predicting short‐term prognosis in older inpatients.